2020
DOI: 10.1101/2020.07.23.218834
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Retinoic acid rewires the adrenergic core regulatory circuitry of childhood neuroblastoma

Abstract: Neuroblastoma cell identity depends on a core regulatory circuit (CRC) of transcription factors that collaborate with MYCN to drive the oncogenic gene expression program. For neuroblastomas dependent on the adrenergic CRC, treatment with retinoids can inhibit cell growth and induce differentiation in both primary neuroblastomas and cell lines; however, the underlying mechanisms remain unclear. Here we show that when MYCN-amplified neuroblastomas cells are treated with all-trans retinoic acid (ATRA), histone H3… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 44 publications
(64 reference statements)
1
5
0
Order By: Relevance
“…This suggest that activation of retinoic acid signaling is not stably maintained in both the responsive cell lines, although even in SH-SY5Y retinoic acid signaling pathway genes remain positively enriched compared to control conditions (Figure 2D withdrawn vs. control) after 96 h of withdrawal, suggesting some level of maintenance or a slow decrease in retinoic acid signaling. This further indicates that BE2C could also revert to the control state after a longer duration, consistent with what was shown recently (Zimmerman et al, 2021). Notably, the normalized enrichment score measuring retinoic acid signaling pathway gene set downregulation is greater in SH-SY5Y than BE2C, reflecting the observation that SH-SY5Y cells retract ATRA-induced neuronal projections and revert, whereas BE2C maintain their differentiated morphology.…”
Section: Differential Transcriptional Changes In Response To Retinoic...supporting
confidence: 90%
See 3 more Smart Citations
“…This suggest that activation of retinoic acid signaling is not stably maintained in both the responsive cell lines, although even in SH-SY5Y retinoic acid signaling pathway genes remain positively enriched compared to control conditions (Figure 2D withdrawn vs. control) after 96 h of withdrawal, suggesting some level of maintenance or a slow decrease in retinoic acid signaling. This further indicates that BE2C could also revert to the control state after a longer duration, consistent with what was shown recently (Zimmerman et al, 2021). Notably, the normalized enrichment score measuring retinoic acid signaling pathway gene set downregulation is greater in SH-SY5Y than BE2C, reflecting the observation that SH-SY5Y cells retract ATRA-induced neuronal projections and revert, whereas BE2C maintain their differentiated morphology.…”
Section: Differential Transcriptional Changes In Response To Retinoic...supporting
confidence: 90%
“…Then, to identify CRC components that define ATRA responsiveness, we identified the regulators in both BE2C and SH-SY5Y cells (Figure 6A). The resulting ATRA responsive CRC contained previously reported ADRN CRC components, including PHOX2B, TBX2, and KLF7 (Boeva et al, 2017;Durbin et al, 2018;Zimmerman et al, 2021), as well as novel candidates CEBPG, KLF13, TWIST1, and FEV, which were identified in the responsive cell lines but not in the ATRA-resistant SH-EP cell line (Figure 6A, Supplementary Figure S6B). According to Boeva et al (2017) andvan Groningen et al (2017), KLF7 is a member of the ADRN CRC.…”
Section: Hic1 and Smad3 Are Part Of The Atra Responsive Crc Of Neurob...mentioning
confidence: 79%
See 2 more Smart Citations
“…Importantly, transcriptional and posttranscriptional regulation determines the final level of N-MYC protein in both MYCN amplified and non-amplified tumors. For instance, enhancer hijacking that repositions a super enhancer close to the affected genes through chromosomal translocation accounts for the high level of C-MYC or N-MYC expression in some neuroblastoma cells without MYCC amplification or without a high MYCN copy number, respectively ( 68 , 69 ).…”
Section: Gene Amplification Of Mycnmentioning
confidence: 99%